Intestinal Anti-inflammatory Effects of Outer Membrane Vesicles from Escherichia coli Nissle 1917 in DSS-Experimental Colitis in Mice - Fábrega, María-José; Rodríguez-Nogales, Alba; Garrido-Mesa, José; Algieri, Francesca; Badía, Josefa; Giménez, Rosa; Gálvez, Julio; Baldomà, Laura (Frontiers in Microbiology, 2017)
Escherichia coli Nissle 1917 (EcN) is a probiotic strain with proven efficacy in inducing and maintaining remission of ulcerative colitis. However, the microbial factors that mediate these beneficial effects are not fully known. Gram-negative bacteria release outer membrane vesicles (OMVs) as a direct pathway for delivering selected bacterial proteins and active compounds to the host. In fact, vesicles released by gut microbiota are emerging as key players in signalling processes in the intestinal mucosa. In the present study, the dextran sodium sulphate (DSS)-induced colitis mouse model was used to investigate the potential of EcN OMVs to ameliorate mucosal injury and inflammation in the gut. The experimental protocol involved pre-treatment with OMVs for ten days before DSS intake, and a five-day recovery period. Oral administration of purified EcN OMVs (5 µg/day) significantly reduced DSS-induced weight loss and ameliorated clinical symptoms and histological scores. OMVs treatment counteracted altered expression of cytokines and markers of intestinal barrier function. This study shows for the first time that EcN OMVs can mediate the anti-inflammatory and barrier protection effects previously reported for this probiotic in experimental colitis. Remarkably, translation of probiotics to human healthcare requires knowledge of the molecular mechanisms involved in probiotic-host interactions. Thus, OMVs, as a non-replicative bacterial form, could be explored as a new probiotic-derived therapeutic approach, with even lower risk of adverse events than probiotic administration.